AUTHENTICITY DEGREE OF CORE FACTS (Proceedings of the YSU C: Geological and Geographical Sciences, 2008)
In the article the subjects about presented facts of geological boreholes of diamond column drilling in ore deposit of effective minerals are discussed. The primary quality index of drilling is the percentage exit of cores, safe keeping of core materials during the drilling. In the forming of core acted different factors of technical and technological characters, natural particularities of shaken rocks, as: splitting, abrasive capacity to resist to the destruction of abrasion ferrule eroded of rocks or core components by washing liquid. By the researches it is installed that the diameter of drilling has not influenced on the exit of the core by the determinate method and the higher exit of core more than 70%, does not guarantee the reliable aspect constrained to the selective abrasion of the easily destructed minerals.
Keywords: diamond column drilling; splitting; abrasive capacity; abrasion eroded of rocks